Variability in Phytophthora capsici (Leonian) isolates of black pepper (Piper nigrum L.) based on nutritional preferences and isozyme profiles - Y R Sarma, Shamina Azeez (Journal of Spices and Aromatic Crops, 2017)
Experiments were conducted to study the intraspecific variability among five isolates ofblack pepper (Piper nigrum) foot rot pathogen, Phytophthora capsici, in its nutritional prefer-ences and isozyme profiles. The carbon sources most suited for the vegetative growth of theisolates were sucrose and glucose, followed by starch, fructose, cellulose and maltose. Amongthe nitrogen sources, the L-isomers of the amino acids, glutamate, proline, aspartate, aspar-agine, histidine, serine, arginine and glycine, and also the organic sources of nitrogen,urea, yeast extract, casein hydrolysate, peptone and tryptone supported good growth. Amongthe vitamins studied, only thiamine was essential for vegetative growth of P. capsici. A con-siderable degree of variation was observed among the five isolates in their preferences fornutrient sources for their optimal growth. From the isozyme profiles of esterase, acid phos-phatase, superoxide dismutase and catalase systems, the similarity between the isolates rangedbetween 25.0%–44.7%.